IDENTIFICATION AND POTENTIAL PARASITES IN NILE TILAPIA (Oreochromis niloticus) CULTURED IN DOLO SUBDISTRICT, SIGI DISTRICT - Manurung, Usy Nora; Wijanarko, Wijanarko; Mauru, Serli; Manurung, Melani; Permana, I Nyoman Adi (Asian Journal of Aquatic Sciences, 2025)
Tilapia (Oreochromis niloticus) is a freshwater aquaculture fish in Dolo District, Sigi Regency. This study aimed to determine the type and prevalence of parasites on tilapia. This research was conducted from June to August 2024. Fish samples were taken in 5 villages: Kota Pulu, Kota Rindau, Potoya, Tulo, and Maku, with each village location taking as many as 10 fish, then parasite examination was carried out at the Central Sulawesi Animal, Fish, and Plant Quarantine Center Laboratory. The method used was smear preparation (smear method) with the target organs being the skin (body mucus) and gills. The total number of samples examined was 50 fish with a length of 10.5-12.8 cm and a weight of 30-43g. The results of parasite identification found nine types of ectoparasites that infect Tilapia, namely Trichodina sp, Dactylogyrus sp, Uronema sp, Oodinium sp, Gyrodactylus sp, Chilodonela sp, Vorticella sp, Chlorosoma sp, Apiosoma sp, and Chichlidogyrus sp. The highest prevalence in Tilapia was in Dactylogyrus sp parasites at 70%, Trichodina sp at 28%, and Gyrodactylus sp at 2%.